2014
DOI: 10.1089/ast.2013.1069
|View full text |Cite
|
Sign up to set email alerts
|

A Conspicuous Clay Ovoid in Nakhla: Evidence for Subsurface Hydrothermal Alteration on Mars with Implications for Astrobiology

Abstract: A conspicuous biomorphic ovoid structure has been discovered in the Nakhla martian meteorite, made of nanocrystalline iron-rich saponitic clay and amorphous material. The ovoid is indigenous to Nakhla and occurs within a late-formed amorphous mesostasis region of rhyolitic composition that is interstitial to two clinopyroxene grains with Al-rich rims, and contains acicular apatite crystals, olivine, sulfides, Ti-rich magnetite, and a new mineral of the rhoenite group. To infer the origin of the ovoid, a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 175 publications
2
25
0
Order By: Relevance
“…The petrographic context of the ferric (oxy)hydroxide (i.e., irregular patches and lamellae with siderite) indicates that it was the last of the three components, and formed by oxidation of the carbonate. This interpretation for the origin of the ferric (oxy)hydroxide agrees with previous reports of alteration of the Nakhla carbonates (Saxton et al 2000;Chatzitheodoridis et al 2014), and Treiman and Gooding (1991) likewise concluded that patches and veinlets of hematite and ferrihydrite were the last of the secondary minerals to have formed in Nakhla veins. The presence within ferric (oxy)hydroxide patches of Si, Cl, and K, which are otherwise absent from the siderite, shows that the fluid responsible for alteration of the carbonates had interacted with preexisting Fe-Mg silicate, and so further supports the sequence of events outlined above.…”
Section: Sequence Of Formation Of the Three Iddingsite Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…The petrographic context of the ferric (oxy)hydroxide (i.e., irregular patches and lamellae with siderite) indicates that it was the last of the three components, and formed by oxidation of the carbonate. This interpretation for the origin of the ferric (oxy)hydroxide agrees with previous reports of alteration of the Nakhla carbonates (Saxton et al 2000;Chatzitheodoridis et al 2014), and Treiman and Gooding (1991) likewise concluded that patches and veinlets of hematite and ferrihydrite were the last of the secondary minerals to have formed in Nakhla veins. The presence within ferric (oxy)hydroxide patches of Si, Cl, and K, which are otherwise absent from the siderite, shows that the fluid responsible for alteration of the carbonates had interacted with preexisting Fe-Mg silicate, and so further supports the sequence of events outlined above.…”
Section: Sequence Of Formation Of the Three Iddingsite Componentssupporting
confidence: 91%
“…; Chatzitheodoridis et al. ), and Treiman and Gooding () likewise concluded that patches and veinlets of hematite and ferrihydrite were the last of the secondary minerals to have formed in Nakhla veins. The presence within ferric (oxy)hydroxide patches of Si, Cl, and K, which are otherwise absent from the siderite, shows that the fluid responsible for alteration of the carbonates had interacted with pre‐existing Fe‐Mg silicate, and so further supports the sequence of events outlined above.…”
Section: Discussionmentioning
confidence: 96%
“…Earth of course still has such conditions; Venus may have harbored such conditions very early on; and there is evidence that Mars at least had surface water in the Noachian. For example, Martian shergottites display signs of aqueous interaction extending to the last few million years, and even now there are vestiges of a water table (Webster et al 2014 ;Cockell 2014 ;Chatzitheodoridis et al 2014 ). Sustained water-rock interaction may also occur on icy moons that host liquid water oceans in contact with a mafic silicate layer, thereby producing chemical disequilibria similar to those likely present on the early Earth (Vance et al 2007;Hsu et al 2015).…”
Section: Generating Geochemical Disequilibria Responsible For the Orimentioning
confidence: 99%
“…therein) of major rock-forming minerals (i.e., px-ol), transformation of plagioclase to maskelynite ( [30] and refs. therein), and formation of melt pockets, veins, and bubbles in the glass [31,32]. Shock features in olivine and pyroxene include planar deformation features, twinning, and mosaicism and these are abundant in both DaG 476 and SaU 005 [33].…”
Section: Introductionmentioning
confidence: 99%